Performance Analysis in ILQ-45 Stock for 2017-2020 Period - Hidayat, Rendra Arief; Wuryani, Eni; Putikadea, Insyirah (Journal of Ecohumanism, 2024)
Research conducted by Fama and French in 1996 showed that there were factors other than the beta that were significantly able to predict stock returns. In other words, the Fama and French Three Factors Model (TFMFF) is better than the Capital Asset Pricing Model (CAPM). However, several subsequent studies showed inconsistent results. The discrepancy between the results of previous studies prompted this research to be carried out. In this study, the researchers selected the stocks used based on the criteria for company profits and return on equity (ROE) offered by Warren Buffett. This study uses Buffett’s criteria in selecting stocks to compare the ability of CAPM and TFMFF to estimate the return of stocks grouped into the Fama & French portfolio. The method used is quantitative. The secondary data used are quarterly close price data, mining company equity value, Bank Indonesia interest rate (risk-free rate), and number of outstanding shares (number of shares outstanding). The results of this study indicate that TFMFF is more accurate than CAPM in predicting stock returns.